Effects of psychological and psychosocial interventions on sport performance: A meta-analysis - Brown, D. J.; Fletcher, D. (Sports Medicine, 2017)
Background: Psychologists are increasingly supporting the quest for performance enhancement in sport and there is a need to evaluate the evidence base underpinning their work. Objectives: To synthesize the most rigorous available research that has evaluated psychological, social, and psychosocial interventions with sport performers on variables relating to their athletic performance, and to address some of the perplexing issues in the sport psychology intervention literature (e.g., do interventions have a lasting effect on sport performance?). Methods: Randomized controlled trials were identified through electronic databases, hand-searching volumes of pertinent journals, scrutinizing reference lists of previous reviews, and contacting experts in the evaluation of interventions in this field. Included studies were required to evaluate the effects of psychological, social, or psychosocial interventions on sport performance in athletes when compared to a no-treatment or placebo-controlled treatment comparison group. A random effects meta-analysis calculating the standardized mean difference (Hedges` g), meta-regressions, and trim and fill analyses were conducted. Data were analyzed at post-test and follow-up (ranging from 1 to 4 weeks after the intervention finished) assessments. Results: Psychological and psychosocial interventions were shown to enhance sport performance at post-test (k = 35, n = 997, Hedges` g = 0.57, 95 % CI = 0.22-0.92) and follow-up assessments (k = 8, n = 189, Hedges` g = 1.16, 95 % CI = 0.25-2.08); no social interventions were included or evaluated. Larger effects were found for psychosocial interventions and there was some evidence that effects were greatest in coach-delivered interventions and in samples with a greater proportion of male participants. Conclusions: Psychological and psychosocial interventions have a moderate positive effect on sport performance, and this effect may last at least a month following the end of the intervention. Future research would benefit from following guidelines for intervention reporting.